KNOWLEDGE AND ATTITUDES REGARDING HIV/AIDS AMONG UNDERGRADUATE STUDENTS AT NAZARBAYEV UNIVERSITY: A CROSS-SECTIONAL STUDY - Ismagulova, Alina (Nazarbayev University School of Medicine, 2025)
Introduction: Human Immunodeficiency Virus (HIV)/ Acquired Immunodeficiency Syndrome (AIDS) continues to be a considerable problem around the world and in Kazakhstan. The rates of infection tend to be rising particularly among young adults thus the need to launch an awareness and prevention drive. Understanding university student’s knowledge and attitude towards HIV/AIDS is a necessary step to create impactful and well-received strategies and stigma reducing interventions. Aims: This study aims to assess the current knowledge and attitudes regarding HIV/AIDS among students at Nazarbayev University and to explore demographic factors associated with the students' knowledge and attitudes toward HIV/AIDS. Methods: A quantitative cross-sectional survey was conducted among 456 undergraduate students from Nazarbayev University. Data were collected via an anonymous online survey after participants were contacted with a request to participate. Demographic characteristics were analyzed using descriptive statistics and the association between demographic traits and HIV/AIDS knowledge and attitude was determined through multiple regression analysis. Results: The study reported a total of 66.7% of students had insufficient knowledge of HIV/AIDS and mean knowledge score was 4.83 (out of 8), which represents moderate level of awareness. Although 70.8% of the students displayed positive attitudes, significant percentages of negative perceptions were seen (29.2%), especially in casual contact with HIV/AIDS patients. Being female, having a high level of knowledge, and sexual experience were associated with a more positive attitude. Conclusions: These results underline an urgent need to implement specific educational strategies that will improve knowledge and influence attitudes about HIV/AIDS among students. University curricula should encompass education on HIV/AIDS, and stigma reduction programs should be implemented for better knowledge and attitudes.
Keywords: Knowledge; Attitudes; Awareness; HIV/AIDS; University Students; Kazakhstan; type of access: embargo